Growth Factor Content in Human Sera Affects the Isolation of Mesangiogenic Progenitor Cells (MPCs) from Human Bone Marrow - Montali, Marina; Barachini, Serena; Panvini, Francesca M.; Carnicelli, Vittoria; Fulceri, Franca; Petrini, Iacopo; Pacini, Simone (Frontiers in Cell and Developmental Biology, 2016)
Mesangiogenic Progenitor Cells (MPCs) are human bone marrow-derived multipotent cells, isolated in vitro under selective culture conditions and shown to retain both mesengenic and angiogenic potential. MPCs also co-isolated with multipotent stromal cells (MSCs) when bone marrow primary cultures were set up for clinical applications, using human serum (HS) in place of fetal bovine serum (FBS). MPC culture purity (over 95%) is strictly dependent on HS supplementation with significant batch-to-batch variability. In the present paper we screened different sources of commercially available pooled human AB type serum (PhABS) for their ability to promote MPC production under selective culture conditions. As the majority of “contaminating” cells in MPC cultures were represented by MSC-like cells, we hypothesized a role by differentiating agents present in the sera. Therefore, we tested a number of growth factors (hGF) and found that higher concentrations of FGF-2, EGF, PDGF-AB, and VEGF-A as well as lower concentration of IGF-1 give sub-optimal MPC recovery. Gene expression analysis of hGF receptors was also carried out both in MSCs and MPCs, suggesting that FGF-2, EGF and PDGF-AB could act promoting MSC proliferation, while VEGF-A contribute to MSC-like cell contamination, triggering MPC differentiation. Here we demonstrated that managing hGF contents, together with applying specific receptors inhibitors (Erlotinib-HCl and Nintedanib), could significantly mitigate the batch-to-batch variability related to serum supplementation. These data represent a fundamental milestone in view of manufacturing MPC-based medicinal products.